A free trade area between the Repbulic of Moldova and the European Union: feasibility, perspectives and potential impact - Ana Popa; Alex Oprunenco; Matthias Lücke; Mahmut Tekce; Hristev Eugen; Georgeta Mincu; Victoria Vasilescu; Valeriu Prohnitchi (Expert-Grup, Centru Analitic Independent, 2009)
This publication has been launched within the project “European Union – Republic of Moldova Trade Relations: Current Situation and Perspectives for Enhancement”. The project is sponsored by the Moldova-Soros Foundation. The major goal of this project is to help Moldovan government formulate and adopt balanced and sound positions for the future negotiations with the European Commission, so that an “enhanced trade regime” contributing to the economic modernization of the country and economic integration with EU is achieved.
Keywords: F14; 330; free trade agreement; feasibility study; Moldova; European Union